The use of English abbreviations on WhatsApp amongst university students in Zimbabwe - Mukenge, Clemenciana (Journal of Modern Languages, 2024)
This study explores the utilization of WhatsApp abbreviations among university students in Zimbabwe and its implications for English language proficiency. Using a mixed-methods approach, combining semi-structured interviews with 30 university students in Zimbabwe and Content Analysis of selected WhatsApp messages, this study investigates the nature, purpose, and implications of abbreviation usage on students’ language skills. The findings reveal that while abbreviations facilitate efficient communication and social cohesion, they also simplify language, reduce vocabulary development and grammatical accuracy, and blur the distinction between formal and informal communication, potentially eroding formal language skills, particularly for non-native English speakers. The study highlights the need for educators to implement a multifaceted approach, incorporating digital literacy, context-dependent language use, vocabulary and grammar development, linguistic flexibility awareness, and balanced communication practices to reconcile digital communication demands with linguistic efficacy goals. These findings have positive and negative implications on students’ overall language proficiency. The study’s limitations include using a relatively small sample (30 students) and focusing solely on WhatsApp abbreviations, excluding other social media platforms. Future studies should aim to recruit a larger sample and explore a broader range of social media platforms.